Pharmacognostical and Phyto Chemical Standardization of Tila kwatha A Polyherbal Formulation - Asokan Vasudevan, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmacognostical and Phyto Chemical Standardization of Tila kwatha A Polyherbal Formulation